Etude de cas : l'utilisation de base de données informatisées sur les incendies de forêt en Italie - Scipioni A. (Les incendies de forêt en région méditerranéenne : constitution et utilisation des bases de données, 1995)
The statistical results on forest fires can be used for many different purposes. Nevertheless, statistical analysis of forest fires has so far been focused mainly on the fire itself within given a region with specific economic and administrative conditions. The information obtained in this way is extremely interesting and useful for the organisation of the fire-fighting agency. But one must have a comprehensive view of the ecological and ethnological aspects and be capable of better identification of causes and of suggesting useful features to formulate possible preventive measures.
Séminaire sur les Incendies de Forêt en Région Méditerranéenne, 1993/11/30-1993/12/04, Montpellier (France)